EFFECTIVENESS OF DIFFERENT TYPES OF PHOTOTHERAPY IN THE TREATMENT OF VITILIGO - Tolibov M.M. (PEDAGOGS, 2024)
Annotation: Vitiligo is characterized by sudden loss of pigment anywhere on the skin. Foci of depigmentation are prone to peripheral growth, appear as a result of a violation of the secretory function of melanocytes or their death. The development of the disease is not accompanied by subjective symptoms, does not pose a threat to life, but is an unfavorable factor that has a serious impact on the quality of life, the psycho-emotional state of the patient, his mood and leads to disruption of social ties and maladaptation. According to WHO, there are up to 40 million people in the world (about 2.8% of the world's population) suffering from this disease.